2010
DOI: 10.1590/s0102-76382010000300020
|View full text |Cite
|
Sign up to set email alerts
|

Espasmo coronariano no pós-operatório de cirurgia de revacularização do miocárdio sem circulação extracorpórea: Diagnóstico e manejo

Abstract: Coronary artery spasm in perioperative of coronary artery bypass graft surgery is a serious complication, with high rate mortality. Patient 51 years-old submitted to coronary artery bypass graft surgery without Extracorporeal Circulation. The patient evolved in 1st post operative (PO) day with enzymatic alteration and ST-elevation, developing soon afterwards in ventricular fibrillation, defibrillation with success. Cardiac catheterization showed important spasm of all coronary arteries and anastomosis between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Reports [1, 2] have showed that autologous arteries rather than veins as bypass graft provide superior long-term outcomes. Moreover, using of LIMA to graft the diseased left anterior descending coronary artery has become the standard method for almost all CABG surgery [3]. However, graft spasm, especially in LIMA with an incidence of at least 0.43% in all CABG surgery [4], and graft stenosis still cause the problem in patients undergoing CABG surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Reports [1, 2] have showed that autologous arteries rather than veins as bypass graft provide superior long-term outcomes. Moreover, using of LIMA to graft the diseased left anterior descending coronary artery has become the standard method for almost all CABG surgery [3]. However, graft spasm, especially in LIMA with an incidence of at least 0.43% in all CABG surgery [4], and graft stenosis still cause the problem in patients undergoing CABG surgery.…”
Section: Introductionmentioning
confidence: 99%